2021
DOI: 10.3390/pathogens10111369
|View full text |Cite
|
Sign up to set email alerts
|

Coffee Pulp, a By-Product of Coffee Production, Modulates Gut Microbiota and Improves Metabolic Syndrome in High-Carbohydrate, High-Fat Diet-Fed Rats

Abstract: Waste from food production can be re-purposed as raw material for usable products to decrease industrial waste. Coffee pulp is 29% of the dry weight of coffee cherries and contains caffeine, chlorogenic acid, trigonelline, diterpenes and fibre. We investigated the attenuation of signs of metabolic syndrome induced by high-carbohydrate, high-fat diet in rats by dietary supplementation with 5% freeze-dried coffee pulp for the final 8 weeks of a 16-week protocol. Coffee pulp decreased body weight, feed efficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…The study found that individuals who lost weight more easily had higher levels of koala bacteria in their gut. In addition to its role in weight loss, this bacterium is a key regulatory factor in maintaining the dynamic balance of intestinal flora [ 46 ]. Therefore, an increase in the relative abundance of its flora may be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…The study found that individuals who lost weight more easily had higher levels of koala bacteria in their gut. In addition to its role in weight loss, this bacterium is a key regulatory factor in maintaining the dynamic balance of intestinal flora [ 46 ]. Therefore, an increase in the relative abundance of its flora may be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Coffee husk is one of the carbohydrate and fiber sources (BlinovĂĄ et al, 2017) with a prebiotic potential that can be absorbed by the host but shows a good effect on microbiota growth in the intestine, such as Lactobacilli and Bifidobacteria, by effectively utilizing feed as the substrate and inducing digestive enzyme secretion, thus increasing gastrointestinal digestion process (Campos et al, 2012;Fiesel et al, 2014;Bhandarkar et al, 2021). This intestinal microflora will produce SCFAs (short-chain fatty acids), namely butyric and propionic acids.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the efficacy of coffee cherry pulp juice concentrate in blood lipid control could have potential application in preventing dyslipidemia and other related diseases. Interestingly, some animal studies using coffee pulp aqueous extract (CPE) also showed benefits in modulating glucose intolerance and hyperlipidemia [ 8 , 30 , 31 , 32 ]. The mechanisms of controlling blood sugar and lipids are likely through the inhibition of intestinal cholesterol absorption [ 8 ] and antioxidative effects from polyphenols such as chlorogenic acid (CGA), epicatechin (EC), and catechin [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%